Enzymatic treatment to increase resistant starch in oat flour - Collinius, Ida (2018)
Oat has been established as a useful crop hundreds of years ago all over the world. Oat contains starch which are compound polyhedral granules built out of amylose and amylopectin. Some of the starch can be resistant depending on type of crop, grade of maturation etc. Starch can be modified by heat and moisture treatment or enzymatic treatments to increase the yield of resistant starch. Resistant starch is defined as starch, or products from starch that is resistant towards digestion and absorption in the small intestine in healthy humans. Instead it can be fermented in the large intestine. Resistant starch occurs in four types depending on process or origin and these are known to have beneficial health effects. The food production enzyme pullulanase derived from microorganisms such as bacillus species has the function of breaking the 1,6-glyosidic linkage in amylopectin, debranching the molecule into straight chains that gives the starch larger opportunity to be converted to resistant starch. The aim of this study was to increase the yield of resistant starch in an oat flour from the company Lantmännen to be able to use it as a food product with a healthy approach. The method was performed on two different materials; oat starch and oat flour and the time setting was 60 minutes and the amount of material was 3 grams or 4 grams. The enzyme pullulanase was used at 50 μl or 100 μl. A rapid visco analyzer (RVA) was set at different temperature and time settings to figure out a good range to give a high resistant starch yield. The method design was divided into 3 programs, first the gelatinization program at 95°C for 15 minutes, second the enzymatic treatment, adding the enzyme pullulanase at 50°C. Finally, the last program was aimed to kill of the enzyme at 95°C. The samples were put in fridge for 12h and then into freezer before freeze-dried and then analyzed with “Megazyme resistant starch assay kit”. The samples were analyzed in a light microscope and the results were calculated in excel. The results showed that the parameters for increasing resistant starch was not as clear as expected. The oat starch samples showed a decisive increase in resistant starch in comparison to oat flour. The results did not show any specific trend for amount of sample or amount of enzyme in the oat flour samples since the resistant starch content was too low to see any trend. In oat starch samples, there was higher yield of resistant starch with more enzyme added. The amount of material used did not show any specific trend. Further research is needed to see if it is possible to increase the resistant starch yield in an industrial process for oat flour.